ANALISIS PENCEGAHAN DAN PENANGGULANGAN HIV/AIDS PADA POPULASI GAY DAN WARIA DI KABUPATEN BANYUWANGI - Erna Agustina; Niko Pahlevi Hentika (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this research is to describe and analyze the implementation of Banyuwangi district Regulation no.5 2017, concerning of HIV/AIDS prevention and control for gay and trangender population. The research method used in this study is descriptive-qualitative. The research results on implementation of HIV/AIDS prevention and control for the gay and transgender population on Banyuwangi : First, the communication aspects carried out by the implementor actors have gone well and can carry out collaborative activities, Second, in terms of general resources, it is said to be sufficient, Third, the disposition aspect of the implementor has been very positive, and Four, the aspects of beurocratic structure, where the divison roles between implementing agencies are very clear. Furthermore, the driving factor of the implementation, is the existence of a good relationship between actors of implementor and a high sense of social concern for the problem of HIV/AIDS among individual implementers. The inhibiting factor is that there are still some members of the population from gay and transgender community, who are still difficult to be given directive and the delays in funding support by the government.